VD_FINDINFO HC / 2013 / 852 vom 13. November 2013 - VD Tribunal cantonal (2013)
FORME AUTHENTIQUE, ABUS DE DROIT, DÉCISION PRÉJUDICIELLE, INCONVÉNIENT MAJEUR, VICE DE FORME | 2 al. 2 CC, 216 al. 2 CO, 285 CPC, 58 al. 3 LNo, 91 LTF, 236 CPC (CH), 237 CPC (CH), 319 let. b ch. 2 CPC (CH)